Preparedness of Final-year Students in Fields of Medicine, Nursing, and Midwifery Regarding Interprofessional Learning - Sakineh Sharifian; Seyedeh Batool Amini; Jalil Kuhpayeh zade; Saeed Raeesi; Nafise Heidari; Zahra Tajik Mirzaee (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objectives: Interprofessional learning (IPL) can create more collaborations among students of different healthcare disciplines. However, this depends on the tendency of students to learn from each other. Given the fact that the attitude of students is recognized as the major factor for the implementation and success of a program, this study aimed to determine the attitude of final-year students in fields of medicine, nursing, and midwifery of Iran University of Medical Sciences, Tehran, Iran toward the implementation of IPL. Materials and Methods: This descriptive and cross-sectional research was conducted on 200 final-year students in the fields of medicine, nursing, and midwifery, who were active in clinical settings and had work experiences in clinical environments. In this research, data were collected using the valid and reliable readiness for inter-professional learning scale (RIPLS), and subjects were selected through convenience sampling. Results: From 200 distributed scales, about 180 questionnaires (response rate=90%) were returned, 80 and 100 of which were filled by students in the fields of medicine, nursing and midwifery, respectively. According to the results, 50.6% of the respondents were female and 49.4% were male. Moreover, mean (standard deviation) total score of the evaluated students was equal to 79.8 (SD=92). Considering the obtaining of a score higher than the desired level by students (57), it could be concluded that the subjects had a positive attitude toward IPL. While the results were indicative of no significant difference between the two medicine and nursing-midwifery groups in terms of preparedness for IPL (P=0.4), there was a significant difference in the subcategory of cooperation and teamwork (P=0.001). In this regard, medical students obtained a lower score, compared to the nursing and midwifery students. Conclusion: According to the results of the study, the subjects had a proper attitude toward IPL, which itself is the most important support for the entrance of this new educational approach in student curriculums.